The leader's guide to storytelling : mastering the art and discipline of business narrative - Denning, Stephen (J-B US non-Franchise Leadership., 2011)
How leaders can use the right story at the right time to inspire change and action. This revised and updated edition of the best-selling book A Leader's Guide to Storytelling shows how storytelling is one of the few ways to handle the most important and difficult challenges of leadership: sparking action, getting people to work together, and leading people into the future. Using myriad illustrative examples and filled with how-to techniques, this book clearly explains how you can learn to tell the right story at the right time.: Stephen Denning has won awards from Financial Times, The Innovat.